Dynamical properties of maps derived from maps with strong negative Schwarzian derivative - Abraham Boyarsky (International Journal of Mathematics and Mathematical Sciences)
A strong Schwarzian derivative is defined, and it is shown that the convolution of a function with a map from an interval into itself having negative strong Schwarzian derivative is a function with negative Schwarzian derivative. Such convolutions have 0 as a stable periodic point and at most one other stable periodic orbit in the interior of the domain.